EFEKTIVITAS PENDAMPINGAN ORANG TUA DALAM PENGGUNAAN MEDIA SOSIAL TERHADAP PERILAKU PADA ANAK DI LINGKUNGAN MASYARAKAT - Dini Pradieta Agustin; Agus Hasbi Noor; Dewi Safitri Elshap (IKIP Siliwangi, 2026)
This study aims to determine the effectiveness of parental guidance on children's social behavior in the community when it comes to social media use. The study is motivated by the increasing use of social media among children, which can have positive and negative impacts on their social behavior development. Parental guidance is considered an important factor in constructively directing social media use.This study uses a mixed-methods approach, combining quantitative and qualitative methods. The quantitative method involves distributing questionnaires to 35 respondents consisting of parents with children ranging in age from elementary school to early adolescence.The qualitative method involves in-depth interviews with selected informants to supplement the quantitative data. The quantitative research results were analyzed using descriptive statistics, and the qualitative data were analyzed thematically.The results indicate that parental guidance regarding social media use positively affects children's social behavior, including their ability to interact, empathy, and social awareness.